Design And Construction of Emergency Pedestrian Egress Tunnels, Essex Junction, Vermont - Bradford F. Townsend; Robin B. Dill; Richard M. Croswell (Society for Mining, Metallurgy & Exploration, 1993)
Innovative geotechnical construction techniques were used to construct three pedestrian tunnels under a building slab-on-grade to allow utilization of basement space for manufacturing. Tunnels were constructed using mining techniques through granular fill soils less than three feet below on-going sensitive manufacturing operations. Project design consisted of jet grout underpinning of exterior foundation walls and an arch of drilled-in grouted horizontal dowels for soil pre-support to limit ground movements during excavation. Permanent tunnel lining consisted of arched steel rib sets and invert struts supported on precast footings encased in cast-in-place concrete slab and side walls and a gunite arch.